'All the arts of a radical agitation': transnational perspectives on British and Irish landowners and estates, 1800–19211. Issue 254 (3rd October 2018) - Tindley, Annie
Abstract: This article examines the perceptions and responses of landed elites towards their evolving territorial, political and social position and interrogates the ways in which these differed across Britain, Ireland and the empire. It considers the utility of a transnational framework in understandings of the landed classes, defining this as a development in which historians seek to take subjects out of national frameworks and into wider settings, to challenge notions of national exceptionalism. It explores its potential to open new directions in the study of landed families and estates during a period of challenge and argues that as a fundamentally transnational class, landed and aristocratic elites must be contextualized beyond the nation.